(untitled) (Altre Modernità, 2020)
The analysis aims to contribute to the study of the current language policy of the People’s Republic of China (PRC) adopting the theoretical perspective of cultural soft power (wenhua ruanshili). Through the critical reading of excerpts from two volumes of the Language Situation in China report, published respectively in 2013 and 2016 by the Department of Language Information Administration of the PRC Ministry of Education, it will reflect on the vision that the Chinese government proposes of the promotion of putonghua, the official language of the PRC, and the building of a harmonious language life as cultural resources. To this end, links between language planning and cultural soft power will be sought after and highlighted from a discursive point of view. The data collected will be interpreted on the basis of the conceptual structure of soft power, as understood in the Chinese context, the regulatory framework targeting the relations between putonghua and linguistic realities that interact with the official language from a disadvantaged position, such as regional varieties, minority languages, and deviations from the standard, and the interactions between these two strategic areas and the concrete implications of the relationship between language and society. The interrelationship between the development of language policies and the increase in cultural soft power found in the narrative produced by the official discourse will trigger the investigation of the reasons determining the framing of delicate language issues in a more fascinating, yet self-evaluative, image.